"But where are the dates?" Dating as a central site of fat femme marginalisation in queer communities. Issue 1 (2nd January 2022) - Taylor, Allison
ABSTRACT: Drawing on interviews with fifteen queer fat femme women and gender nonconforming individuals, I explore queer fat femmes' negotiations of dating in contemporary queer communities in Canada. Using thematic analysis to analyse the interviews, I identify how queer fat femmes' experiences of dating in queer communities are often characterised by rejection and fetishisation. These experiences have significant and negative impacts, generating feelings of undesirability, fear, and failure. I connect the marginalisation of queer fat femmes in queer dating contexts to the reproduction and circulation of fatphobia and femmephobia in queer communities. Finally, I suggest that queer fat femmes' responses to their marginalisation in queer dating contexts reflect resilience, as they find ways to navigate their oppressions and fulfill their needs.